Interações potenciais entre AINEs prescritos em endodontia e medicamentos em uso pelos pacientes odontológicos - Bée, Lais Regina (2015)
The non-steroidal anti-inflammatory drugs (NSAIDs) are widely used in Endodontics and when associated with some risk factors, such as concomitant use of other drugs, may develop undesirable and possibly serious effects. This cross-sectional study evaluated, through data collecting on dental records, potential interactions among the most commonly prescribed NSAIDs and medications used by patients treated in the Integrated Clinical Dentistry of UFSM, from 2007 to 2011. The data were processed on the EpiData and the statistical analysis was performed with SPSS Software. For analysis of interactions between drugs two tertiary bibliographic source were used: the book Drug Interaction Facts and computerized tool Drugdex in the Micromedex. Potential drug interactions with NSAIDs occurred with 20.2% of the drugs related by patients. The most common consequences in this context were gastrointestinal bleeding, decrease antihypertensive effect and renal failure. In relation to gravity and documentation of interaction, there was a higher frequency of the important gravity and well-documented in the issue of pharmacological interaction. Hence, special attention must be given to the elderly and other patients using several drugs at the same time alongside with educational initiatives focused on a more safe prescription method should be taught in educational institutions.